Effect of Straw Throwing Method and Some Operational Parameters on the Performance of a Small Rectangular Baler - Affan O. Hussein (Polytechnic Journal)
The experiment was carried out on a private farm in Karak village in 2017 to study the effects of the method of throwing the straw behind the combine harvester and some operational factors on the performance of a small rectangular baler. The field was planted with wheat (Triticum spp.) and barley (Hordeum vulgare). A small rectangular baler type (Ćicoria 454), Italian made was used to pick up and bale the straws, which were thrown as heaps and windrows in the field. The results obtained showed that picking up the straw as windrows improved the baler’s performance over the heaps in terms of number of mechanical units stops, time require for baling, fuel consumption, baler’s throughput capacity, and baler’s throughput efficiency, on the other hand, the forward speed also affected the baler’s performance when the straw was thrown as windrows; By increasing the forward speed, the slippage percentage increased but the fuel consumption, baler’s throughput efficiency, and baler’s throughput capacity decreased.